Social support in health workers: trends in national productions (Research, Society and Development, 2022)
Objective: to identify trends in national scientific productions of theses and dissertations regarding social support in health care workers. Method: this is a narrative review of the literature, carried out in the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel. The search was performed in July 2021, through strategy, "social support" and health workers. No time cut. The search resulted in 115 productions, of which 08 studies were included. Results: of the eight productions included in the study, 100% (n=08) were dissertations. From that, we distinguished two categories for analysis and discussion: product characterization and trends regarding social support. The impact of social support on the health of workers in their work environment and its correlation with suffering, illness, stress, presenteeism and intention to leave the profession were identified. Final considerations: It evidenced tendencies of the relation of social support with the worker's health, since this acts as a health protector under harmful effects when present in the work environment. It was observed that when it is low, it can potentiate the development of work-related diseases and decrease the quality of life of professionals. The results of this study allowed us to identify that there are still scientific gaps in the national productions about social support among primary care workers, being an important area of investigation. It is important to address the theme in this context, contributing to the health of the worker, with a view to developing strategies to promote actions that strengthen social support.